Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan PT Sumber Terang Agro Lestari di Teluk Tenggulang Kec. Tungkal Ilir Kab. Banyuasin Sumatera Selatan - Yadi, Nopri (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
The purpose of this study is to analyze the affect compensation and work motivation on the performance of employees of PT. Sumber Terang Agro Lestari in Teluk Tenggulang Kec. Tungkal Ilir Kab. Banyuasin south sumatera. The data used in this study were primary data obtained from questionnaires faild ouy by 38 respondents. The research results prove thet compensation (X1) and motivation (X2) have a significan positive effect on employee performance (Y). Research is expected to be useful for companies to inprove employee performance through compensation and work motivation.